Epidemic Characteristics of Histomonosis in Geese Flocks in the Orenburg Region - I. Khristianovsky , Pavel; A. Platonov, Stanislav; V. Belimenko, Vladislav (KnE Life Sciences, 2021)
In May-June 2019, there was a mortality surge among adult geese on the IP Samodurov farm (in the village of Krasnokholm, Orenburg Region). The deaths stopped as soon as the geese were out of lay. Pathological and microbiological studies established three parasitic diseases in the flock: heterakidosis, histomonosis, and eimeriosis. A one-off seasonal and age-related manifestation of these diseases is due to a reduced body resistance in the winter, huddling behaviour, and a high load in female geese during the laying season. Keywords: histomonosis, epidemic characteristics, eimeriosis